Formulation and Physical Characteristics Evaluation of Sargassum sp. Lip Gel for the Exfoliative Cheilitis Treatment - Carmaylia Athallah Ferawati; Cindy Pratiwi Djumadi Putri; Erlin Ardiyanti Kurniawan; Syahna Najla Nur Alya; Rima Parwati Sari; Anjelin Tjioe (Universitas Muhammadiyah Yogyakarta, 2025)
Exfoliative cheilitis is a disease that often occurs, especially in Indonesia, exacerbated by hot weather and vehicle exhaust pollution, which can cause dry and cracked lips. The components found in Sargassum sp. are beneficial in enhancing the effectiveness of vitamin C, aiding skin regeneration, and potentially acting as antioxidants to combat free radicals. To develop a lip care formulation from Sargassum sp. seaweed to overcome the problem of exfoliative cheilitis. Sargassum sp. was crushed and extracted to produce three kinds of formulations that tested for homogeneity using methylene blue, which was dripped on each replication on a watch cup and stirred until a homogeneous mixture between the oil and water content. Viscosity was tested using a Brookfield viscometer, the organoleptic assessment was done visually, the pH test was performed using a pH meter, occlusivity was tested using filter paper, the stability test was evaluated using a centrifuge, and the adhesion test was conducted using an adhesion test tool. The study results revealed in the organoleptic test that the form of the three formulations was the gel form, with transparent yellowish to yellowish brown color. At the same time, the aroma was slightly pungent, which is typical of Sargassum sp. (F1-2). In the viscosity test, there were significant differences between preparations F1(48.740±408.412), F2(9.420±274.955), and F3(2200±91.652). In the pH test, there were significant differences between F1(5.657±0.019), F2(6.838±0.058), and F3(8.960±0.112). All formulations were homogeneous and stable after centrifugation for 30 minutes in the homogeneity and stability tests. In the occlusivity test, there was no significant difference in preparations F1-3, and only significant differences were found in the occlusivity test at 24 and 48 hours in the F3 formulation. In the adhesion test, there were significant differences between F1(2.4367±0.168), F2(2.1467±0.127), and F3(1.3467±0.145). Formulations 1 and 2 met the gel preparation test criteria, while formulation 3 did not meet the gel preparation test criteria.